Políticas de extensão em universidades privadas paulistanas: análise das práticas em psicologia sob o enfoque da psicologia social comunitária - Fiedler, Regina Célia do Prado (2007)
The present thesis examines, with the participatory methodologies inherent in the theoretical-practical conception of Community Social Psychology, the social application of Psychology related to policies in the extension (out-reach) sectors of private universities in the city of São Paulo. This study is justified due to the growing number of professionals that graduate from this type of university and that can use extension activities as a space for differentiated preparation, critical and transforming the socio-historical determinants of society. We seek to use policy analysis and practices of the extension sector as a locus-synthesis of the institutional crisis of hegemony and legitimacy through which the universities find themselves in general and the specificities in the private Brazilian universities. To this end, semi-structured interviews were conducted with university officers responsible for the extension services of private universities and psychology professors that conduct community interventions. Discourse analysis was used to reflect over the uses and meanings attributed to those practices in the university, organized under the influence of neo-liberal educational policies. The analysis brought elements of reflections on how private universities define their social functions: we observed in the interviews with vice-rectors or directors of extension services that the lack of preparation and/or specific information about social management causes the majority of officers to assume the management of extension services as a place for community assistance or social marketing. The absence of a discourse about extension services, allied to the lack of institutional autonomy (in the majority of cases studied there was not a specific budget for extension services) and the lack of interest by the institutions where the main elements that are reflected in our analysis of the discourses in this sector. On the other hand, the analysis of the extension projects implemented by psychologists showed that the majority of professors that work on these extension projects do not understand the area as a locus for social transformation, but rather as a place for practical application of knowledge without the intent of involving the population in an active proposition for social transformation. Scientific knowledge prevails over the process of dialogically constructing knowledge, in which the student, in many projects, only executes the project as elaborated by the professors in which the community is only viewed as the target population. This demonstrates that Social Psychology and its participatory instruments have not been sufficiently consolidated in the practices of these universities